Descripción del proceso constructivo sus características e importancia de los materiales y equipos usados en el revestimiento con hormigón armado bombeable, caso: túnel de descarga del proyecto hidroeléctrico mina San Francisco, cantón Pucará, provincia del Azuay. - Ordoñez Macas, Alfonso Javier (2015)
pumpable armed Tunnel Hydroelectric Project Download Minas-San Francisco. For the preparation of this work titling an investigation we were conducted, being used the following: investigate, collect, observe, record, describe and compare. interviews, bibliography research, technical specifications, field studies, observation and photographs: For data collection the following techniques were used. Already done this work titration was concluded that the "Austrian Method" consisting primarily of excavation after sustaining phase and as a last step, the final coating with reinforced concrete used in the construction of this tunnel, is the most appropriate because it conforms to the characteristics and conditions of the site where is located the work as well as it can ensure that the chosen method is more flexible because it allows us to make modifications to the original design as delete function structural whereby the thickness was reduced by the coating on the hearth and the coating was removed in the vault; and also it concluded that materials are added as additives, cement, reinforcing steel, scabs, etc. and equipment such as pump concrete, formwork, etc. If they meet all the requirements that are set in the technical specifications of the project.